تأثير مستوى الجلد النفسي على مستوى التوافق النفسي المهني عند الممرضين العاملين بمصلحة مكافحة السرطان - صلعة, حفصة (كلية العلوم الاجتماعية لجامعة مستغانم, 2024)
هدفت هذه الدراسة إلى تناول الجانب النفسي لدى الممرضين بمستشفى السرطان ومعرفة إذا كان الجلد النفسي يؤثر على مستوى التوافق النفسي المهني لديهم، كذلك معرفة إذا كان عامل الأقدمية والخبرة المهنية يؤثران على التوافق النفسي المهني، أيضا معرفة إذا يؤثر عامل السن على مستوى الجلد. ومن أجل يتم تحقيق الأهداف المذكورة أعلاه، تم استخدام المنهج العيادي وعينة قصدية ذات خصائص تلائم موضوع الدراسة التي تمثلت في 4 حالات، 3إناث وذكر كانت أعمارهم تتراوح ما بين 27سنة إلى 60 سنة وكذلك تم الاعتماد على الملاحظة العيادية ودليل المقابلة ومقياس الجلد النفسي CD-RISC، وذلك من أجل التأكد من صحة فرضيات الدراسة وتوصلني إلى النتائج التالية: - يؤثر مستوى الجلد النفسي على مستوى التوافق النفسي المهني عند الممرضين العاملين بمستشفى السرطان. - يؤثر عامل الخبرة المهنية على مستوى التوافق النفسي المهني عند الممرضين بمستشفى السرطان. - كلما ارتفع عامل السن ارتفعت معه نسبة الجلد
دراسة عيادية لأربع حالات بمستشفى عين تادلس مستغانم
This study aimed to study the psychological aspect of nurses in a cancer hospital and find out if psychological well-being affects their level of psychological-professional adjustment، as well as knowing if the factor of seniority and professional experience affects psychological-professional adjustment، and also knowing if age affects their level of psychological-professional adjustment. In order to achieve the above-mentioned goals، the clinical approach and a purposive sample with characteristics appropriate to the subject of the study were used، which consisted of 4 cases، 3 females and a male، whose ages ranged from 27 years to 60 years. Also، reliance was placed on clinical observation، an interview guide، and the CD-RISCResilience. In order to verify the validity of the study’s hypotheses، I reached the following results: - The level of psychological resilience affects the level of professional psychological adjustment among nurses working in a cancer hospital. - The factor of professional experience affects the level of professional psychological adjustment among nurses in a cancer hospital. - The higher the age factor، the higher the resilience
Keywords: الجلد النفسي – التوافق النفسي المهني-الممرضين بمستشفى السرطان.; The resilience – professional psychological compatibility – nurses in the cancer hospital